Dynamics Of Japanese Foreign Direct Investment (JFDI) In Electronic And Electrical (E&E) Manufacturing Sector In Malaysia - Tan, Swee Ean (2011)

(untitled)
This research focuses on the dynamics of JFDI in E&E manufacturing sector particularly the significance changes and the potential development in Malaysia This study commenced with significant statistical data from Toyo Keizai Data Bank 2008 revealing the trend of JFDI and its essential catalytic role in E&E manufacturing function, employment, R&D, export and import particularly in China, NIEs and ASEAN. Penyelidikan ini berfokus kepada perubahan aliran masuk PTA Jepun yang signiftkan dan pembangunan sektor pembuatan E&E yang berpotensi di Malaysia. Kajian ini bennula dengan analisis statistikal data dari Toyo Keizai Data Bank 2008 yang menunjukkan pola PTA Jepun dan peranannya dalam fungsi pembuatan E&E, pekeijaan, Penyelidikan dan Pembangunan (P&P), import dan eksport terutamanya di negera China, NIEs dan ASEAN.